Understanding the traditional wisdom of harvesting rainwater in household yards: construction and rainwater usage patterns of settlement water cellars in semi-arid China. Issue 2 (4th March 2023) - Zhou, Weinan; Matsumoto, Kunihiko; Sawaki, Masanori
ABSTRACT: This study focuses on the heritage users and artisans of water cellars – the principal source of potable water in semi-arid China for centuries – to examine their construction and rainwater usage patterns. The main advantages of water cellars are their low construction cost, user-friendly technology, and water usage stabilization features. The concrete impermeable layer was introduced by artisans in 1970, but residents' and artisans' preferences for raw material differ. Furthermore, the survey results showed that the daily average water-use per person was 28.5 L, when there was no drought and harvested rainwater was used for bathing. In contrast, about 14 L of water per person is required daily, when usage is kept to a minimum for bathing and laundry, in the event of a drought. The wisdom behind such adjustments is irrefutable, but it is inadequate to alleviate the discomfort of extreme water-saving. This evidence-based awareness of the advantages of water cellars – as well as the limitations of traditional wisdom – will facilitate their sustainable development.